Features of industrial development in the regions of the Republic of Kazakhstan - Abdimomynova, А.Ш.; Talapbayeva, Г.Е.; Utegenova, K.A.; Alibekova, A.B.; Temirbekova, E.T. (BUKETOV BUSINESS REVIEW, 2017)
The article summarizes the possibilities of the program for the development of regions in the development of Kazakhstan's industry. The authors note that according to the technical level, the level of automation and mechanization, the complexity and depth of processing of raw materials, environmental indicators and energy intensity, the existing production of Kazakhstan lag markedly behind advanced production abroad. Therefore, tools for state regulation of industrial modernization processes are needed. At present, the state indirectly affects the activities of industrial enterprises. The authors, considering the output of industrial products by region, argue that the efficiency of economic activity depends equally on the channels of supply of raw materials and materials, and on the availability of markets. In the opinion of the authors of the article, the main problem of innovative development is, on the one hand, the weak interest of business in the implementation of innovative projects, on the other hand, the lack of financial and other opportunities for developing and introducing the latest technologies and equipment for many enterprises in the real sector of the economy. These aspects of public administration will be governed by a renewed regional policy that should be able to optimally mobilize the resources and potential of regions depending on the specialization of industry. The authors proposed the basics of industrial policy aimed at progressive changes in the structure of industrial production in accordance with selected national goals and priorities.